LIFE DRAMAS OF AN INSURGENT SURGEON «PASTEUR» (BASED ON THE MATERIALS OF THE COURT CASE OF THE BRANCH ARCHIVE OF THE SSU): TO THE 80TH ANNIVERSARY OF THE FOUNDATION OF THE UKRAINIAN INSURGENT ARMY - I.D. Lyubchyk (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
Considering this year's challenges of the war and the anniversary date - the 80th anniversary of the foundation of the Ukrainian Insurgent Army, we want to draw attention to the forgotten insurgent figures, whose activities were focused not so much on the military struggle, but on the struggle for human life. The article's purpose is to reveal the pages of life in the insurgent underground at that time, not yet a certified surgeon, «Pasteur». For the first time, we will try to do this through the court case of Oleksiy Mykolayovych Zelenyuk, from the branch archive of the SSU in the Ivano-Frankivsk region. His life is the drama of an unconquered Ukrainian who was born in Vinnytsia, studied and began his medical practice in Odesa, led the insurgent struggle against the occupation regimes in a white coat in Stanislav region (now Ivano-Frankivsk region), and after severe wanderings in exile, continued his medical practice in Lviv Region. Key words: Ukrainian insurgent army, «Pasteur», Oleksiy Zelenyuk, surgeon, insurgent hospital, Red Cross, Prykarpattia.